The Hybrid Library: The Focal Point of Traditional and Digital Libraries - Mehdi Afzali (Türk Kütüphaneciliği)
Many libraries are currently experiencing a transition from traditional print- based collections to one that holds a mix of print and digital resources. This has led to the existence of so called hybrid libraries. A hybrid library conjugates elements of the traditional and the digital library. The most basic challenge is to acquire a common understanding of their definitions, aims, and missions. Digital and hybrid libraries are two kinds of modern libraries, defined as different entities. Definitions of these libraries show some overlap. So, it is notpossible to separate them as two completely different types of libraries. The aim of this paper is to investigate the practices of and challenges confronting hybrid and digital libraries.